The Development of the Rantepao Town Square Area as an Integrated Cultural Tourism Destination in North Toraja - Meidy Putri Utami; Nasrullah; Ni Nyoman Harnika (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to identify the physical and non-physical potential of the Rantepao Town Square area, analyze its existing conditions based on the 4A tourism components, and formulate development directions for the area as an integrated cultural tourism destination in North Toraja. Method: A qualitative case study approach was used, collecting data through direct field observations, documentation, and in-depth interviews with site managers, the Tourism Office, visitors, local communities, artists, and traders. Data were analyzed using the interactive model with source and method triangulation. Result: Empirical evidence confirms strong cultural appeal anchored by the Pongtiku Monument, Tongkonan inspired museum housing traditional mummies, and authentic Alang, positioning the square as North Toraja’s central urban cultural gateway. However, development as an integrated destination is constrained by multi-dimensional gaps: spatial-functional parking conflicts, unmaintained basic amenities, physical damage to the Art Center, lack of cultural interpretation trails, and fragmented governance without formal MSME inclusion. To bridge these gaps, a phased development roadmap with defined implementation stages, responsible stakeholders, and measurable indicators was formulated, prioritizing short-term functional fixes (0–1 year), medium-term informational/economic integration (1–3 years), and long-term Art Center revitalization (3–5 years). Contribution: This study contributes to destination management literature by examining the integration of cultural heritage and urban open spaces. Practically, it offers strategic recommendations for sustainable heritage preservation and local economic enhancement.